Efektivitas Konten Media Sosial Tiktok @Pandawaragroup Sebagai Media Kampanye Membersihkan Lingkungan - Dwi Yanti; Dwi Maya Lestari; Noerma Kurnia Fajarwati (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
Human survival depends on the environment. However, the lack of human awareness in protecting the environment has caused a lot of destruction to occur. To increase human awareness and understanding, Pandawara uses TikTok social media to provide information as well as appeal to people to preserve the environment. This research aims to measure and analyze the effectiveness of TikTok social media content presented by the @PandawaGrup account as a campaign tool to increase public awareness and participation in efforts to clean the environment and the responses that occur therein. The researcher used a qualitative descriptive research method which was implemented by monitoring and analyzing the @pandawagrup account evenly. The results of this research are that the social media TikTok @pandawagrup as a campaign media in protecting the environment is considered to have a significant role because it is able to share advocacy information about the environment and there are positive impacts that emerge which can be seen from the large number of positive responses both in terms of the number of likes and good opinions in awareness of protecting the environment.